Literatos en 90 minutos. (Pack 1), (Borges, Nabokov, Beckett, García Márquez, James Joyce y Heminway) - Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2017)
The Pack Literatos 1 collection brings together 6 of the twentieth century literati who changed, among others, literature.
Borges en 90 minutos -- Nabokov en 90 minutos -- Beckett en 90 minutos -- García Márquez en 90 minutos -- James Joyce en 90 minutos -- Hemingway en 90 minutos.
This collection of books by Strathern were published separately in print. The publisher now combined them by subject and published them together in digital format.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed February 7, 2019)
Keywords: Borges, Jorge Luis, -- 1899-1986.; Nabokov, Vladimir Vladimirovich, -- 1899-1977.; Joyce, James, -- 1882-1941.; Hemingway, Ernest, -- 1899-1961.; Beckett, Samuel, -- 1906-1989.; García Márquez, Gabriel, -- 1927-2014.; Authors -- Biography; Biographies; Electronic books